(untitled) (Biological Sciences - PJSIR, 2022)
The lipid content of primary roots (10, 20, and 30 mm) and the respective cotyledons were determined according to Folch’s method [7,8] (Table I) and the lipids were classified into neutral and polar lipids by TLC [9,10] using different solvent systems (Table 2).